INTEGRATING ARTIFICIAL INTELLIGENCE TECHNOLOGIES INTO EDUCATION: AN ANALYSIS OF OPPORTUNITIES AND CHALLENGES (International journal of artificial intelligence, 2026)
Artificial Intelligence (AI) has become an important technology in modern healthcare and medicine. AI systems are widely used in medical diagnostics, disease prediction, robotic surgery, and patient monitoring. This study examines the role of AI in improving healthcare quality and efficiency. The research is based on analytical and qualitative methods using scientific literature and healthcare reports. The findings show that AI increases diagnostic accuracy, reduces human error, and supports personalized treatment. However, challenges such as data privacy, ethical concerns, and technological limitations remain significant issues. Overall, AI has strong potential to transform global healthcare systems and improve patient outcomes in the future.